Proteus - West, Morris (Glasgow William Collins Sons & Company Ltd., 1979)
A fictional investigation of the dilemma faced by modern man when confronted with increasing social violence.
English Fiction.
Keywords: Terrorism -- English fiction -- Political prisoners